2018
DOI: 10.1007/s10096-018-3193-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between duration of intravenous antibiotic administration and early-life microbiota development in late-preterm infants

Abstract: Antibiotic treatment is common practice in the neonatal ward for the prevention and treatment of sepsis, which is one of the leading causes of mortality and morbidity in preterm infants. Although the effect of antibiotic treatment on microbiota development is well recognised, little attention has been paid to treatment duration. We studied the effect of short and long intravenous antibiotic administration on intestinal microbiota development in preterm infants. Faecal samples from 15 preterm infants (35 ± 1 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(108 citation statements)
references
References 34 publications
4
103
0
1
Order By: Relevance
“…A recent research revealed that AMX mediated opportunistic pathogen Escherichia/Shigella blooms persisted 42 days after the interruption of antibiotic therapy [22]. Similar phenomenon was also reported by Zwittink and colleagues, who also discovered that 5 days treatment with AMX and ceftazidime combinations allowed Enterococcus to thrive and remain dominant for up to two weeks and caused Bifidobacterium abundance to remain decreased till postnatal week six after antibiotic treatment discontinuation [51]. Therefore, our results demonstrated the serious negative side-effect of AMX could be persistent and colon region-different, which should be considered as an important aspect of the risk assessment for AMX prescription.…”
Section: Amx Effects Were Colon Region-different and Persistentsupporting
confidence: 67%
“…A recent research revealed that AMX mediated opportunistic pathogen Escherichia/Shigella blooms persisted 42 days after the interruption of antibiotic therapy [22]. Similar phenomenon was also reported by Zwittink and colleagues, who also discovered that 5 days treatment with AMX and ceftazidime combinations allowed Enterococcus to thrive and remain dominant for up to two weeks and caused Bifidobacterium abundance to remain decreased till postnatal week six after antibiotic treatment discontinuation [51]. Therefore, our results demonstrated the serious negative side-effect of AMX could be persistent and colon region-different, which should be considered as an important aspect of the risk assessment for AMX prescription.…”
Section: Amx Effects Were Colon Region-different and Persistentsupporting
confidence: 67%
“…Because microbiota perturbation during infancy may be disproportionately damaging 35,36 , it is imperative to study the lasting effects of antibiotics and hospitalization on the preterm IGM. Prior studies of preterm infants report IGM recovery concomitant with NICU discharge [37][38][39] . However, these studies rely on culture or amplicon sequencing (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Since bifidobacteria are considered beneficial early life colonisers of the gut, this is a point of concern. Bifidobacteria play an important role in milk digestion, limit pathogen colonisation and support development of the immune system . As shown previously, a lower abundance of bifidobacteria during early development of the gut microbiota may also be a result of postpartum antibiotic use rather than of two vancomycin doses .…”
mentioning
confidence: 76%